La fraseografia toscana - Massimo Fanfani (Linguistik Online, 2024)
Tuscan phraseography had its first moment of success between the 16th and 17th centuries. Numerous collections of proverbs and sayings were compiled during this time, although not all were printed. In the 19th century, idiomatic expressions began to be distinguished from proverbs and were excellently arranged in Giuseppe Giusti’s Raccolta di proverbi toscani (1853).